Perbandingan PONV Pada Pasien yang Diberikan Ondansetron Sebelum Spinal Anestesi dan Sesudah Spinal Anestesi di RSUD Wates - Vrilia Adira Sari; Astika Nur Rohmah; Nia Handayani (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Postoperative Nausea and Vomiting (PONV) is a common complication following surgery, including procedures involving spinal anesthesia, which can increase patient discomfort and length of hospital stay. Ondansetron is effective in preventing PONV, but its effectiveness may depend on the timing of administration. This study aimed to compare the incidence of PONV in patients who received ondansetron before and after spinal anesthesia at RSUD Wates. A comparative quantitative method was used with 40 respondents. Data were analyzed using the Mann–Whitney test, which showed a significant result of 0.003 (p < 0.05). In the group receiving ondansetron before spinal anesthesia, 5 respondents (25%) experienced mild nausea and 15 respondents (75%) reported no nausea or vomiting. In contrast, in the group receiving ondansetron after spinal anesthesia, 7 respondents (35%) reported no symptoms, 6 respondents (30%) experienced nausea only, and 7 respondents (35%) experienced vomiting or retching. It can be concluded that administering ondansetron before spinal anesthesia is more effective in preventing PONV.